Precipitation isotopes from West Africa (Benin and Senegal) - Christine Vallet-Coulomb; Anne Alexandre (PANGAEA, 2025)
Triple oxygen isotope composition of precipitation events collected at Nalohou (NA, Benin) and Dahra (DA, Senegal) in 2018 and 2019. The water was analyzed by Cavity Ring Dow Spectroscopy (CRDS). Annual averages weighted for precipitation amount are presented.
In: Alexandre, Anne (2025): Climate and triple oxygen isotope of precipitation, groundwater, soil water, plant water, and phytolith data from West Africa (Benin and Senegal) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984133